Psychological resilience as a mediator between transformational leadership and work engagement - Siska Siska; Suryani Hardjo; Amanah Surbakti (Indonesian Institute for Counseling, Education and Theraphy, 2026)
This study aims to examine the role of resilience as a mediating variable in the relationship between transformational leadership and work engagement among banking employees in Indonesia. This research is motivated by high work demands, service pressures, and rapid organizational changes in the banking sector, so that organizational and psychological factors are needed to maintain employee work engagement. The study used a quantitative approach with a correlational design involving employees from one of the national private banks in North Sumatra. Data were collected using standardized psychological instruments to measure transformational leadership, resilience, and work engagement, then analyzed using Partial Least Squares Structural Equation Modeling. The results show that transformational leadership has a positive effect on work engagement and self-resilience, while self-resilience also has a positive effect on work engagement. In addition, resilience has been shown to mediate the relationship between transformational leadership and work engagement. These findings indicate that supportive and inspirational leadership plays an important role in increasing employee work engagement, both directly and through strengthening individual adaptive capacity.